Immunogenic cell death-based cancer vaccines: promising prospect in cancer therapy - Wang, Jiandong; Ma, Jinyuan; Xie, Fangyuan; Miao, Fengze; lv, Lei; Huang, Yueying; Zhang, Xinyue; Yu, Junxia; Tai, Zongguang; Zhu, Quangang; Bao, Leilei (Frontiers in Immunology, 2024)
Tumor immunotherapy is a promising approach for addressing the limitations of conventional tumor treatments, such as chemotherapy and radiotherapy, which often have side effects and fail to prevent recurrence and metastasis. However, the effectiveness and sustainability of immune activation in tumor immunotherapy remain challenging. Tumor immunogenic cell death, characterized by the release of immunogenic substances, damage associated molecular patterns (DAMPs), and tumor associated antigens, from dying tumor cells (DTCs), offers a potential solution. By enhancing the immunogenicity of DTCs through the inclusion of more immunogenic antigens and stimulating factors, immunogenic cell death (ICD) based cancer vaccines can be developed as a powerful tool for immunotherapy. Integrating ICD nanoinducers into conventional treatments like chemotherapy, photodynamic therapy, photothermal therapy, sonodynamic therapy, and radiotherapy presents a novel strategy to enhance treatment efficacy and potentially improve patient outcomes. Preclinical research has identified numerous potential ICD inducers. However, effectively translating these findings into clinically relevant applications remains a critical challenge. This review aims to contribute to this endeavor by providing valuable insights into the in vitro preparation of ICD-based cancer vaccines. We explored established tools for ICD induction, followed by an exploration of personalized ICD induction strategies and vaccine designs. By sharing this knowledge, we hope to stimulate further development and advancement in the field of ICD-based cancer vaccines.